Influence of developmental stage on the antibiotic resistome and virome of the critically endangered kākāpō (Strigops habroptilus) - Ayriss, Natalie; West, Annie G.; French, Rebecca K.; Geoghegan, Jemma L.; Chatterton, James; Digby, Andrew; Uddstrom, Lydia; , Kākāpō Recovery Team; Taylor, Michael W. (Frontiers in Microbiology, 2025)
Endemic to Aotearoa New Zealand, the kākāpō is among the world’s rarest bird species with a current population of less than 250 individuals. As part of ongoing research efforts to support the conservation of this intensively managed species, we utilised a metatranscriptomics approach to elucidate, for the first time, the expression of antibiotic resistance genes within the kākāpō chick and adult gut microbiomes, further leveraging these data to describe the kākāpō virome. To determine differences among members of the kākāpō population, our data were obtained from birds encompassing different ages, sexes, geographic locations and antibiotic histories. We additionally analysed a time-series dataset following a single male kākāpō over the course of antibiotic treatment during a case of exudative cloacitis. There were significant differences between chicks and adult kākāpō in both the expression of antibiotic resistance genes and their viromes. Expression of these genes indicated potential resistance against 32 antibiotic classes, including 14 single classes of antibiotic and 18 multidrug classes. We identified 74 viral families, but no known avian-infecting viruses. Our case study of the single kākāpō during antibiotic treatment revealed notable changes in expression across time, with a reassuring lack of antibiotic resistance gene expression towards the end of the treatment, indicative of continued efficacy of antibiotic treatment. These novel data will help to inform conservation efforts for this enigmatic and unique bird species.